Seymour/carraher's polymer chemistry - Jr., Charles E. Carraher ([S.l.] : CRC Press, 2003)
This revolutionary and best-selling resource contains more than 200 pages of additional information and expanded discussions on zeolites, bitumen, conducting polymers, polymerization reactors, dendrites, self-assembling nanomaterials, atomic force microscopy, and polymer processing. This exceptional text offers extensive listings of laboratory exercises and demonstrations, web resources, and new applications for in-depth analysis of synthetic, natural, organometallic, and inorganic polymers. Special sections discuss human genome and protonics, recycling codes and solid waste, optical fibers, self-assembly, combinatorial chemistry, and smart and conductive materials.
Keywords: cHEMISTRY